Modelling genetic polycystic kidney disease using human pluripotent stem cell-derived kidney organoids - Liu, Meng (Nanyang Technological University, 2023)
Polycystic kidney disease (PKD) is an inherited disorder characterized by progressive expansion of fluid-filled cysts in the kidney. Autosomal dominant polycystic kidney disease (ADPKD) and autosomal recessive polycystic kidney disease (ARPKD) represent the most common forms of PKD. Treatment options are limited due to lack of models to faithfully recapitulate PKD pathophysiology. Herein, we generated a collection of kidney organoids from both PKD patient-derived iPSCs and genetically engineered hPSCs, alongside stress paradigm, to emulate PKD cystogenesis. Cyst formation within PKD kidney organoids exhibited a myriad of structural and functional abnormalities that are typically manifested in PKD patients. Patient iPSC-derived kidney organoids developed tubular cysts in vivo upon engraftment into the sub-renal capsule space of immunocompromised mice. We also performed a small-scale drug screening and identified two candidate drugs that can effectively attenuate cyst formation in both ARPKD and ADPKD kidney organoids. Mechanistic studies revealed that autophagy plays critical roles in safeguarding PKD kidney organoid from cyst formation. The PKD kidney organoid model offers a versatile platform for understanding disease mechanism, as well as for shortlisting drugs with clinical potential.